2020
DOI: 10.9734/ajess/2020/v8i130210
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception towards Mathematics and Its Effects on Academic Performance

Abstract: Aim: The research sought to find out the perception of students towards Mathematics and how it affects their academic attainment in a Ghanaian context. Study Design: Descriptive survey design was used for the study. Methodology: The main instrument used for the study was questionnaire. The sample size for the study comprised of students selected from the three SHSs in Kumasi metropolis using purposive sampling approach. The sample size for the students consisted of 297 students selected by stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 0 publications
1
10
2
1
Order By: Relevance
“…Ampadu also stressed that students' beliefs and perceptions have the potential to either facilitate or inhibit learning. Hagan et al (2020) concluded that students have positive perception towards mathematics when they used 297 students selected via stratified sampling with questionnaire as the main instruments for collecting data in Ghana. Similarly, Daud et al (2020) purpose was to examine students' perceptions in learning mathematics and how these perceptions contributed to problems in comprehending mathematics among some selected Malaysian Secondary School students.…”
Section: Studies On Students' Perception Towards Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ampadu also stressed that students' beliefs and perceptions have the potential to either facilitate or inhibit learning. Hagan et al (2020) concluded that students have positive perception towards mathematics when they used 297 students selected via stratified sampling with questionnaire as the main instruments for collecting data in Ghana. Similarly, Daud et al (2020) purpose was to examine students' perceptions in learning mathematics and how these perceptions contributed to problems in comprehending mathematics among some selected Malaysian Secondary School students.…”
Section: Studies On Students' Perception Towards Mathematicsmentioning
confidence: 99%
“…However, the data revealed that perceptions of mathematics were more neutral in nations with a high degree of technical and industrial growth. In a descriptive survey design, Hagan et al (2020) reported that there was a very weak and negative relationship between students' perception and achievements in mathematics when they used 180 males and 117 females as the sample. Similarly, Daud et al (2020) who examined students' perceptions in learning mathematics and how these perceptions may contribute to problems in comprehending mathematics among some selected Malaysian secondary school's students.…”
Section: Relationship Of Students' Perception Towards Mathematics and Their Achievement In Mathematicsmentioning
confidence: 99%
“…Mathematics is perceived by society as the foundation for scientific and technological knowledge that is cherished by societies worldwide and seen as an instrument for political, socioeconomic, scientific and technological developments (Hagan et al, 2020). To this end, more periods are allotted for Mathematics lessons throughout the world than any other subject, and with teaching come assessment for gauging the extent to which learning has been achieved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the benefits that the study of Mathematics offers, many students perceive it to be difficult (Kislenkoet al, 2007;Lucas & Fugitt, 2009;Wasike et al, 2013;Mutodi & Ngirande, 2014); devote inadequate time to self-practice (Michael, 2015;Assen, 2020); are taught by under-qualified teachers (Ogbonnaya, 2007;Sa'ad, 2014); endure under sourced teaching and learning environments (Lillian & Josephat, 2018); resulting in poor performance in the subject. Thus, most students find it difficult to acquire the different mathematical skills and processes that are useful in their everyday lives (Hagan et al, 2020;Assen, 2020). It is commonly accepted that Mathematics is difficult, obscure, and of little interest to certain people (Eshetu et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sometimes students do not understand the usefulness of mathematics and some even consider it to be a complicated subject, which already predisposes them to it. As [36] point out in a study of 297 students in several senior secondary schools in Ghana, students often have a positive perception of mathematics because they think it is used in everyday life, but they consider it difficult. On the other hand, some see mathematics as an isolated set of procedures with no real-life applications [37], which discourages them from learning.…”
Section: Introductionmentioning
confidence: 99%